Unlocking Firm Profitability Through Governance Architecture: Financial Perspectives - Mamay Komarudin (Danadyaksa: Post Modern Economy Journal, 2026)
This investigation explores the extent to which corporate governance structures shape the earnings performance of consumer goods firms listed on the Indonesia Stock Exchange (IDX) over the 2017–2024 period. The core constructs examined include advertising intensity, market share, the board effectiveness score (BES), financial leverage (DER), and the quality of external auditing as captured by Big 4 affiliation. Drawing on a balanced panel of nine IDX consumer goods companies, this study employs Seemingly Unrelated Regression (SUR), a choice justified by the cross-equation residual correlation of r = −0.506 detected across two structural models. Coefficient stability was verified through three supplementary procedures: robust regression using the Huber M-estimator, a 1,000-iteration bootstrap of OLS coefficients, and quantile regression anchored at the median. Every one of the seven hypotheses reached statistical significance at the 95–99% confidence level. Within the first equation where BES is the outcome variable, advertising intensity (β = 6.609; p < 0.001), market share (β = 3.976; p < 0.001), ROE (β = 17.267; p < 0.001), and leverage DER (β = 7.044; p < 0.001) all produced positive and significant effects (R² = 91.9%). In the second equation, BES (β = 0.035; p < 0.001) and Big 4 audit quality (β = 0.478; p < 0.05) each elevated ROE, whereas market share exerted a significant negative drag (β = −0.170; p < 0.001), yielding R² = 81.5%. Governance quality and profitability are meaningfully intertwined, lending empirical support to agency theory, signaling theory, and resource dependence theory within emerging market settings.